(untitled) (SCIÉNDO INGENIUM, 2022)
The Servir Law No. 30057 began to be implemented since 2013, giving as a last deadline to the country’s public institutions, the year 2018, to begin their incorporation process. Its objective was to determine the relationship that exists between the variable the implementation of the law serve 30057 and its relationship with the work performance of public servants in the Provincial Municipality Sánchez Carrión, with respect to the methodology, the type of study was descriptive-correlational, it is a type of quantitative research its research design is non-experimental, Using the deductive-inductive method, as a technique I use the survey and instrument the questionnaire. Concluding that exists between the variable implementation of the Servir Law 30057 and the variable work performance of public servants of the provincial municipality of Sánchez Carrión is: "moderate positive correlation, in the year 2018. With a Pearson chi-square value of 0.000, since it is less than 0.05 in terms of the validity of the questionnaire, I reach in the independent variable a Cronbach’s alpha value of 0.557 acceptable on the other hand for the dependent variable I achieved a value of 0.586 also acceptable, for data collection.